Two Typical Hereditary Charts of Congenital Factor VII Deficiency - Cleton, F. J; Loeliger, E. A (Thrombosis and Haemostasis, 1961)
The inheritance of congenital factor VII deficiency was investigated in 2 unrelated families. Out of 68 individuals, 4 (3 proven and 1 highly probable) were found to have severe factor VII deficiency (<C 0.1% factor VII), and 29 appeared to be heterozygotes (30—60% factor VII). The coagulation defect is due to an autosomal gene of intermediate expression and complete penetrance. The recessive character of the haemorrhagic diathesis due to the homozygous state for the abnormal gene is clearly demonstrated.